Enhancing the impact performance of reinforced composites through fiber hybridization—A hybrid dynamic shear-lag model. (August 2021) - Liu, Junjie; Wei, Xiaoding
Abstract: In this study, we establish the hybrid dynamic shear-lag model to systemically investigate the effects of reinforcement heterogeneity on the impact performance of hybrid composites. Two key parameters – linear stiffness and linear density of the reinforcement – are found to play critical roles. To optimize the energy absorption, the hybrid unit cell should employ reinforcements with the same linear density but different linear stiffness. Further, tailoring the properties and geometries of constituents ( e.g., the viscosity of the matrix) could greatly enhance the total energy absorption while avoiding severely localized energy distributions in the matrix. Our model provides feasible optimization guidance to the hybrid composites design for ballistic-proof applications.